Demografischer Wandel und Mobilitätsentwicklung. Auswirkungen auf den Fernstraßenbau. - David, Andrea; Kugele, Wolfgang; Ratzenberger, Ralf (Deutscher Verkehrs-Verl., 2007)
In der demografischen Entwicklung Deutschlands sind in langfristiger Betrachtung deutliche Veränderungen zu erwarten. Zum einen wird die gesamte Einwohnerzahl ab etwa 2020 abnehmen. Zum anderen - und noch bedeutender - wird die Zahl der älteren, unterdurchschnittlich mobilen Personen steigen, während die Zahl der überdurchschnittlich mobilen Personen in den mittleren Altersgruppen sinkt. Daraus könnte abgeleitet werden, dass die gesamte Mobilität in Deutschland langfristig zurückgeht. Die Überprüfung dieser These ist Gegenstand des Beitrags, der eine Zusammenfassung einer im Juli 2006 abgeschlossenen Studie im Auftrag des Allgemeinen Deutschen Automobil-Club e.V. (ADAC), München, darstellt. difu

A long-term review of Germany's demographic evolution leaves us to expect significant changes. From 2020 onward, the overall population is expected to decrease while the number of elderly persons - below average mobility - will grow. The number of persons in the middle age group - with above average mobility - is likely to diminish. It can thus be deduced that Germany's overall mobility is going to witness a reduction in the long run. Age-related mobility rates of certain socio-demographic population groups will continue to grow, and - in the case of elderly persons - the growth rate will be above average. Beyond 2020, there will still be strong demand for first class trunk roads, a factor that generates the need right now to secure higher levels of investment in the trunk road network on account of the time-consuming planning and realization process. The anticipated demographic changes can, under no circumstances, justify a standstill or even a reduction in investments. difu
Keywords: Verkehr; Mobilität; Verkehrsprognose; Verkehrsplanung; Personenverkehr; Bevölkerungsprognose; Bevölkerungsentwicklung; Altersstruktur; Wirkung; Bundesfernstraßenbau; Demographischer Wandel